A Durable Response With the Combination of Nivolumab and Cabozantinib in a Patient With Metastatic Paraganglioma: A Case Report and Review of the Current Literature - Economides, Minas P.; Shah, Amishi Y.; Jimenez, Camilo; Habra, Mouhammed A.; Desai, Monica; Campbell, Matthew T. (Frontiers in Endocrinology, 2020)
Introduction: Pheochromocytomas and sympathetic paragangliomas (PPGL) are neuroendocrine catecholamine-secreting tumors that are usually localized. Metastatic disease is rare and systemic treatment consists of conventional chemotherapy and high-specific-activity iodine-131-MIBG which was approved by the FDA in 2018. Although chemotherapy combinations still have value in specific settings, the debilitating side effects of treatment with only modest benefit have limited their use. With the introduction of a new generation of targeted therapy and immunotherapy patients with metastatic PPGL may have improved therapeutic options. Areas covered: The current paper presents a case of a patient with metastatic PPGL who received multiple lines of systemic treatment. Despite progression on previous single agent cabozantinib and single agent pembrolizumab on separate clinical trials, the patient has exhibited a major response to the combination of cabozantinib and nivolumab for the past 22 months. In addition, we will review the available therapies for metastatic PPGL and discuss novel agents under clinical development. Conclusion: Newer targeted therapies and immunotherapy options are under clinical development with promising results for patients with PPGL.